Penguatan Ketahanan Pangan di Masa Pandemi Covid-19 Melalui Pengembangan Produk Lokal dan Pemanfaatan Pekarangan - Muhammad Tasbih Zulhamdi; Rizki Fauzi; Atri Astuti Listiya Athar; Fitrah Alamsyah; Rahmat Ramdani; Iis Wantari; Citra Musafira Isni Wahid; Wahidah Radya Syahfitri; Lisa Iha Rodiah; Wina Nurlisyana; Soni Trison (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
Mura Village is one of the villages located in Brang Ene District, West Sumbawa Regency. This village has 3 hamlets, namely Buin Banyu hamlet, Mura hamlet, and Tegaran hamlet. Most of the people of Mura Village work as farmers, with the greatest potential, namely rice and corn cereals. There are several fundamental problems faced by Mura Village, including limited Human Resources (HR) as indicated by the low productivity of land in the village. Poor household waste management is evidenced by the large amount of organic waste that is wasted every day. The lack of stretching of the creative economy sector is evidenced by the small number of MSMEs in the village so that the people in the village tend to be more consumptive. Before going into the field, KKN-T students are first provided with knowledge of regional potential and community empowerment materials so that program implementation can run well. The existence of directives from the government regarding health protocols during the Covid-19 pandemic made community empowerment programs a little different from usual. Several community empowerment programs include utilizing yards for food security and developing local commodities for food security. The results obtained during the Community Service Program had a very positive impact on the people of Mura. Students are also able to teach residents how to cultivate in buckets (Aquaponics) and about 70% of the village community applies this cultivation method, in the same program there is also distribution of seeds to the dasa wisma gardens and the culmination of a competition to use the house yard and dasa wisma garden which followed by the dasa model homestead group in the village. Furthermore, the students held a workshop on the processing of local commodities in the form of cassava which is processed into mocaf flour which has high added value, the results of the workshop were directly applied by the village government through PKK women to make Mura village a center for making mocaf flour. Keywords: mura village, yard, home industry, mocaf flour